Harmonic Scalpel Assisted Superficial Parotidectomy. (September 2014) - Muhanna, Nidal; Peleg, Uri; Schwartz, Yehuda; Shaul, Hanan; Perez, Ronen; Sichel, Jean-Yves
Objective: The Harmonic Scalpel (HS) has been recently widely used to perform a variety of surgical procedures. We reviewed our experience with the use of HS in superficial parotidectomy to determine the safety and efficacy of this procedure, with regard to operative time, postoperative facial nerve function, and drainage output. Study Design: Nonrandomized retrospective review. Materials and Methods: The medical records of all patients who underwent superficial parotidectomy for benign pathology at Shaare Zedek Medical Center from January 2006 to July 2009 were retrospectively reviewed. Patients with prior facial nerve weakness or prior parotid surgery or who had undergone concurrent neck dissection or total parotidectomy were excluded. Results: Fifty-eight patients were reviewed; 26 patients underwent HS parotidectomy and 32 patients underwent conventional (cold knife) parotidectomy (control group). Harmonic Scalpel assisted parotidectomy was associated with significantly decreased length of surgery from 163.12 ± 21.8 minutes for controls to 137.3 ± 18.6 minutes in the HS assisted group ( P < .05). The incidence of temporary postoperative facial nerve paresis was significantly reduced from 43% in the controls to 23% in the HS group ( P < .05). No permanent facial nerve paralysis was reported. There were differences in the overall postoperative drain output between the HS and control groups, 68 ± 22.3 mL and 73.5 ± 38.2 mL, respectively, but these differences did not achieve significance. Conclusion: This study shows that HS assisted superficial parotidectomy for benign pathology is a safe technique and associated with reduced surgical time and incidence of temporary postoperative facial nerve paresis compared with conventional techniques.